Ablation characteristics and incidence of steam pops with a novel, surface temperature‐controlled ablation system in an ex vivo experimental model. Issue 12 (27th October 2022) - Tsutsui, Kenta; Mori, Hitoshi; Kawano, Daisuke; Tanaka, Naomichi; Ikeda, Yoshifumi; Sumitomo, Naokata; Iwanaga, Shiro; Nakano, Shintaro; Muramatsu, Toshihiro; Matsumoto, Kazuo; Kato, Ritsushi
Abstract: Background: A novel irrigation catheter (QDOT MICRO™) has been introduced, which enables a surface temperature‐controlled ablation combined with tip cooling. However, the detailed description of its complex behavior and effect on the incidence of pops and lesion formation remains elusive. This study aimed to systematically investigate the ablation characteristics, feedback behavior, and incidence of steam pops in a simplified ex vivo swine model. Methods: Using swine ventricular tissue perfused with saline at 37°C, we systematically created lesions with 4×3 combinations of the wattage (20, 30, 40, and 50 W) and contact force (CF, 10, 30, and 50 g). Ablation was continued for either 120 s or until a steam pop occurred and repeated 10 times with each setting. The lesion geometry, ablation index, feedback dynamics, and conditions underlying the steam pops were measured and analyzed. Results: Steam pops occurred particularly frequently in combinations of a low CF and high power (10 g vs. 30 g+50 g [ p  < .0001]; 40 W+50 W vs. 20 W+30 W [ p  < .0001]). Failure to activate a feedback process was associated with a 5.1 times higher incidence of steam pops (21/109 vs.11/11, [95% CI 3.499–7.716], p  < .0001). The wattage feedback was particularly evident with a high CF (30 and 50 g) and high initial wattage (40 and 50 W). The average delivered wattage at 27 W predicted the occurrence of steam pops. Conclusion: The temperature‐controlled ablation with the QDOT MICRO™ demonstrated a complex feedback behavior, which contributed to a reduced incidence of steam pops and prolonged lead time to the pops.